Oocyte quality in women with thalassaemia major: insights from IVF cycles. (July 2019) - Mensi, Laura; Borroni, Raffaella; Reschini, Marco; Cassinerio, Elena; Vegetti, Walter; Baldini, Marina; Cappellini, Maria Domenica; Somigliana, Edgardo
Abstract: Background: Women with thalassaemia major typically experience hypogonadotropic hypogonadism because of the toxic effects of iron overload on the anterior pituitary. Moreover, in affected women, serum anti-Mullerian hormone (AMH) and antral follicle count (AFC) are also shown to be reduced, suggesting that the peripheral excess of iron could also harm the ovarian reserve. To date, the detrimental effects of the disease on oocyte quality have not been investigated. Materials and methods: Women with thalassaemia major who underwent in vitro fertilization (IVF) cycles were retrospectively identified over a 9 years period. They were matched (with a 1:5 ratio) by study period and age to a control group of infertile women undergoing IVF. Embriological variables were compared between the two groups. The primary outcome was the rate of top quality embryos. Results: Twenty-one women with thalassaemia major (exposed group) and 105 controls (unexposed group) were ultimately included. Serum AMH was 0.6 [0.2–1.8] and 1.5 [0.7–3.5] ng/ml, respectively (p = 0.05). AFC was 4 (1–7.5) and 11 (5.5–16), respectively (p < 0.001). The total dose of gonadotropins used was higher in exposed women but the number of retrieved oocytes and oocytes used did not differ. The fertilization rate was higher in exposed compared to unexposed women, being 100% (76–100%) and 75% (50–100%). respectively (p = 0.03). The cleavage rate was also higher, being 75% (39–100%) and 50% (29–64%), respectively (p = 0.04). In contrast, the rate of top quality embryos did not differ, being 20% (0–76%) and 25% (5–50%), respectively (p = 0.98). Conclusions: Despite lower ovarian reserve, oocyte quality is not significantly affected in women with thalassaemia major.